Customer Satisfaction as a Mediator of Service Quality and Perceived Value in Building Customer Trust - Muliyati Muliyati; Rahmat Jaya (Jurnal Ilmiah Manajemen Kesatuan, 2025)
As an archipelagic country with more than 17,000 islands, Indonesia relies heavily on-air transportation for efficient inter-regional mobility. The aim of this study is to examine the role of customer satisfaction in mediating the relationship between service quality and perceived value on customer trust. This study used a quantitative method with 215 respondents. Data was analyzed using the Structural Equation Model (SEM) with SmartPLS 3.0. The results show that customer satisfaction, service quality, and perceived value have a significant effect on customer trust. Furthermore, customer satisfaction has been proven to mediate the relationship between service quality, perceived value, and customer trust. This study is expected to provide empirical evidence for future research and contribute to the development of knowledge in marketing management, particularly regarding the variables of customer satisfaction, service quality, perceived value, and customer trust. The practical implication suggests that customers will be satisfied when the quality of service meets their expectations.